The Effect of Using the SQ3R Method Assisted by Digital Story Texts on Improving Critical Thinking Skills in the 'World Window Book' Material for Grade V Students of SD Negeri 104202 Bandar Setia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effect of using the Survey, Question, Read, Recite, Review (SQ3R) method assisted by digital story texts on students' critical thinking skills in the material